Tantrums in Early Childhood Due to Permissive Parenting - Vernanda Kartika Putri; Ayong Lianawati; Ade Shyl Vionalita Ameilsya Prameswari; Afiefah Syafni Lokasthiti; Deviani Putri Ismawati; Whina Amarsanda Priehayudha; Rose Indah Noviyantie (Journal of Education and Counseling (JECO), 2023)
Tantrums are a common behavioural problem experienced by young children, which can result from various factors, including permissive parenting practices. This qualitative case study aims to explore the forms of tantrums displayed by 6-year-old children, identify the factors contributing to these tantrums, and examine the efforts made by parents with permissive parenting styles to manage their children's tantrums. The research design involves descriptive qualitative methods, utilizing observation, interviews, and documentation techniques for data collection. Data triangulation is applied to ensure the reliability and validity of the findings. The study reveals that tantrums exhibited by the children in the study include crying, hitting, kicking, screaming, and more. The factors leading to tantrums encompass unfulfilled desires, reprimands, neglect, and teasing. The parents' response to these tantrums involves always fulfilling the child's wishes, even when aggressive behaviour is displayed. Furthermore, parents refrain from providing clear explanations to correct negative behaviour. Sometimes, parents let the child continue their tantrum until it subsides without intervening. These findings highlight the presence and consequences of permissive parenting practices on children's emotional development and behavioural patterns.